1981
DOI: 10.1677/joe.0.0880219
|View full text |Cite
|
Sign up to set email alerts
|

Cell Replication in the Islets of Langerhans of Adult Rats: Effects of Pregnancy, Ovariectomy and Treatment With Steroid Hormones

Abstract: It was possible to vary the replication rate of cells in the islets of Langerhans of adult rats. The rate of incorporation of [3H]thymidine into islet DNA was increased at 12 days of pregnancy to 2.3-fold and at 19 days of pregnancy to 1.3-fold that in control rats. Ovariectomy, which leads to lowered plasma levels of ovarian steroids, induced a significant and unexpected increase in the rate of thymidine incorporation into islets; treatment of ovariectomized rats with 2 micrograms oestradiol/rat per day for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
2
2

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 11 publications
4
16
2
2
Order By: Relevance
“…All in all, it appears that progesterone treatment promotes proliferation of already differentiated endocrine cells, rather than the process of differentiation of non-endocrine stem cells to endocrine cells. This situation is similar to the condition of pregnancy, where increased progesterone levels (36) are associated with increased islet-cell proliferation (10,(37)(38)(39) and not with islet neogenesis (40).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…All in all, it appears that progesterone treatment promotes proliferation of already differentiated endocrine cells, rather than the process of differentiation of non-endocrine stem cells to endocrine cells. This situation is similar to the condition of pregnancy, where increased progesterone levels (36) are associated with increased islet-cell proliferation (10,(37)(38)(39) and not with islet neogenesis (40).…”
Section: Discussionsupporting
confidence: 54%
“…of these gonadal factor(s) might also explain the discrepancy between the stimulation of islet-cell proliferation by progesterone in vivo, as shown in the present study, and the inhibitory effects of progesterone on islet-cell proliferation in vitro (12)(13)(14), under which conditions such factors are absent.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Adult ␤-cell proliferation has been observed among pregnant and obese individuals for whom the demand for insulin is increased (40). During ␤-cell or pancreatic injuries, mitotic activity of ␤ cells is also increased (4,6,7,20,22,40). It has been suggested that after injury, ␤-cell regeneration may be the result of progenitor cell proliferation and differentiation (5).…”
mentioning
confidence: 99%
“…Pregnancy entails increased -cell proliferation with an associated increase in -cell mass, which attains a maximum at the end of pregnancy (Hellman 1960, Hellerström 1963, Van Assche 1974, Green et al 1981, Marynissen et al 1983, Parsons et al 1992, 1994. Placental lactogen, growth hormone and prolactin have emerged as the main candidates for mediating pregnancy-specific changes in the -cells (for a review, see Sorenson & Brelje 1997).…”
Section: Discussionmentioning
confidence: 99%